THE DECISION MAKING FOR RICE CONSUMER PURCHASE THE DECISION-MAKING BY THE CUSTOMER IN PURCHASING OF RICE - Yuli Purbaningsih; Helviani Helviani; Nursalam Nursalam; Hasbiadi Hasbiadi; Masitah Masitah; A. Mardiana (International Journal of Multidisciplinary Research and Literature, 2023)
Especially for rice consumers, the demand for rice is based on a need, desire and ability. In addition to having a decision-making process for buying rice, introducing the need for information seeking, evaluating alternatives, purchasing process and post-purchase behavior. The aim of this study is to determine the post-purchase evaluation results of rice for the first purpose and second purpose to determine the purchasing decision-making process for rice consumers in Lamedai Village, Tanggetada District, Kolaka Regency. The data analysis method used is descriptive using the Engel Model or the EKB Model (Engel, Kollat, Blackwell). The results showed that consumers' rice purchasing decision process consists of five stages: need recognition, information seeking, evaluation of alternatives, purchasing decisions and post-purchase evaluation